The potential for long-term cost-effectiveness of obesity prevention interventions in the early years of life - Brown, Vicki; Ananthapavan, Jaithri; Sonntag, Diana; Tan, Eng Joo; Hayes, Alison; Moodie, Marj (Pediatric obesity, 2019)
Background Early childhood obesity prevention is gaining increasing importance, as the prevalence of children with overweight and obesity aged 5 years and under increases worldwide. Along with understanding the effectiveness of obesity interventions, it is important to understand the cost-effectiveness of interventions over time. Objectives To estimate the long-term health benefits and health care cost-savings of reductions in BMI for the Australian population of children aged between 2 and 5 years. Methods A proportional multistate, multiple cohort lifetable model estimated the health benefits and health care cost-savings related to hypothetical reductions in BMI, informed by a scoping review of systematic reviews reporting the effectiveness of obesity prevention interventions in preschool aged children. Results Results suggest significant potential for cost-effectiveness of obesity prevention interventions in preschool-aged children if intervention effect can be maintained. A relatively small population level reduction in BMI z-score (−0.13 BMIz) in children aged 2 to 5 years would result in 36 496 health-adjusted life years saved (95% uncertainty interval [UI], 30 283-42 945) and health care cost-savings of approximately $301 million (95% UI $234 million-$369 million) if modelled over the lifetime. Conclusions Scenario results highlight the importance of obesity intervention in the early years of life.